2017
DOI: 10.2147/ott.s142974
|View full text |Cite
|
Sign up to set email alerts
|

Increased histone deacetylase 6 expression serves as a favorable prognostic factor for diffuse large B-cell lymphoma

Abstract: ObjectiveThis study aims to investigate ectopic expression of histone deacetylase 6 (HDAC6) in diffuse large B-cell lymphoma (DLBCL).MethodsThis study analyzed patients with DLBCL (n=132) and reactive lymph node hyperplasia (n=32) diagnosed in our hospital from December 2007 to May 2016. Correlation between HDAC6 expression and clinical pathologic features was analyzed by χ2 test. The significant differences between the 5-year overall survival (OS) or progression-free survival (PFS) and high HDAC6 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Various groups have reported elevated expression of chromatin modifiers HDACs particularly HDAC6 in B-cell lymphomas compared to normal B-cells which can be directly correlated with disease progression. Inhibition of HDAC6 with selective inhibitor provided survival benefits to CLL in euTCL1 mouse model [173,174]. Importantly, inhibition of HDAC and PI3K signaling together with CUDC-907, a dual HDAC-PI3K inhibitor showed profound activity in ibrutinib-resistant MCL cell lines and PDX mouse models [175].…”
Section: Chromatin Modifiersmentioning
confidence: 99%
“…Various groups have reported elevated expression of chromatin modifiers HDACs particularly HDAC6 in B-cell lymphomas compared to normal B-cells which can be directly correlated with disease progression. Inhibition of HDAC6 with selective inhibitor provided survival benefits to CLL in euTCL1 mouse model [173,174]. Importantly, inhibition of HDAC and PI3K signaling together with CUDC-907, a dual HDAC-PI3K inhibitor showed profound activity in ibrutinib-resistant MCL cell lines and PDX mouse models [175].…”
Section: Chromatin Modifiersmentioning
confidence: 99%
“…Similarly, high mRNA and/or protein HDAC6 expression levels are noted in esophageal squamous cell cancer, pancreatic cancer and lung adenocarcinoma [ 94 , 95 , 96 ]. In contrast, immunohistochemistry (IHC) analysis revealed that in diffuse large B-cell lymphoma (DLBCL) and breast cancer, high HDAC6 expression correlated with better overall, progression-free and disease-free survival, respectively; and overall survival in high-grade serous ovarian cancer (HGSOC) [ 97 , 98 , 99 ]. However, Yano et al reported that IHC analysis of advanced HGSOC patient samples, high HDAC6 expression was associated with poorer overall and progression free survival [ 100 ].…”
Section: Is Hdac6 Expression Disease-relevant In Uveal Melanoma Tissues?mentioning
confidence: 99%